Auditing, Management Games, and Accounting Education (Book). - Zeff, Stephen A.; Grawoig, Dennis E.; Cook, John W. (The Accounting Review, 1966)
Reviews the book "Auditing, Management Games, and Accounting Education," by Neil C. Churchill, Merton H. Miller and Robert M. Trueblood.